1999
DOI: 10.1073/pnas.96.16.9021
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase promotes phospholipase C-γ1 activity

Abstract: The nonreceptor tyrosine kinase FAK (''focal adhesion kinase'') is a key mediator of integrin signaling events controlling cellular responses to the extracellular matrix, including spreading, migration, proliferation, and survival. Integrin-ligand interactions stimulate FAK tyrosine phosphorylation and activation of FAK signaling functions. Here evidence is presented that the FAK autophosphorylation site Tyr-397 mediates a direct interaction with the C-terminal Src homology 2 domain of phospholipase C (PLC)-␥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
133
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 56 publications
6
133
0
3
Order By: Relevance
“…It is particularly significant that Y397 is the responding site because this site is central to the formation of complexes based on the binding of SH2 domains to its phosphorylated form. The SH2 domains of src, PI3-kinase, PLC␥, Grb7, and Shc have been reported to bind pY397 providing many potential downstream signaling consequences (Schaller et ., 1994;Schlaepfer and Hunter, 1997;Han and Guan, 1999;Reiske et al, 1999;Zhang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is particularly significant that Y397 is the responding site because this site is central to the formation of complexes based on the binding of SH2 domains to its phosphorylated form. The SH2 domains of src, PI3-kinase, PLC␥, Grb7, and Shc have been reported to bind pY397 providing many potential downstream signaling consequences (Schaller et ., 1994;Schlaepfer and Hunter, 1997;Han and Guan, 1999;Reiske et al, 1999;Zhang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly significant that Y397 is the responding site because this site is central to the formation of complexes based on the binding of SH2 domains to its phosphorylated form. The SH2 domains of src, PI3-kinase, PLC␥, Grb7, and Shc have been reported to bind pY397 providing many potential downstream signaling consequences (Schaller et , 1994;Schlaepfer and Hunter, 1997;Han and Guan, 1999;Reiske et al, 1999;Zhang et al, 1999).Most current integrin signaling data has been interpreted in the context of the integrin-clustering model. The plating of fibroblasts on a fibronectin-coated surface induces not only the binding of ␣5␤1 to fibronectin, but also the progressive organization of ␣5␤1 into focal contacts and focal adhesions during the process of cell spreading (Singer et al, 1988;Pankov et al, 2000).…”
mentioning
confidence: 99%
“…The genes coding for cmyc epiotope-tagged FAK and FAK Y397F were PCR-amplified from the pRC/CMV-c-myc FAK expression plasmids kindly provided by Dr. Steven K. Hanks [44] and ligated into the pMSCVneo expression vector as restriction fragments at the HpaI-to-BglII site. The mouse fibroblast retroviral packaging cell line, PT67, was transfected with the pMSCVneo/c-myc-FAK plasmids using the TransIT-3T3 transfection kit purchased from Mirus Corp. (Madison, WI).…”
Section: Retrovirus Construction and Hmsc Transductionmentioning
confidence: 99%
“…The N-terminal SH2 domain of PLC-γ1 is known to play a major role in the association with the activated growth factor receptor, while the C-terminal SH2 domain is considered to play a minor role (Chattopadyay et al, 1999;Poulin et al, 2000). However, recently, it has been reported that the C-terminal SH2 domain of PLC-γ1 is involved in interactions with synaptojanin (Ahn et al, 1998), the actin-cytoskeleton (Pei et al, 1996), PIP 3 (Bae et al, 1998;Rameh et al, 1998) and FAK (Zhang et al, 1999). These observations suggest that the two SH2 domains of PLC-γ1 are dissimilar and may mediate the recognition of specific phosphorylation sites.…”
Section: Activation Of Plc-γ γ γ γ1mentioning
confidence: 99%